The Relationships Between Social Institutions, Social Capital and Their Effects on Poverty Reduction - Slamet, Yulius (2010)
This study works on three major variables. The variables are social institution, social capital, and the relationships between the two in an effort to reduce poverty. The aim is to investigate the causes of poverty, in particular among the urban poor of Kelompok Swadaya Masyarakat in Surakarta, Indonesia. There are five objectives which were utilized as a guide. The objectives touches on identifying the patterns and causes of poverty, the discovery of social institutions, the discovery of reasons provided by the respondents on their state of poverty and how they utilized the components embodied in the social capital. Thus the hypotheses employed were there a significant correlations and effects of bonding, bridging and linking social capital pertinent towards poverty reduction. Hence, from this notion, reasons for the state of poverty could be learnt from the past experiences of the particular group. In the investigation, triangulation research methods were used to answer the research questions. In the process, survey research method was used to investigate the patterns of both existing social capital and the state of poverty, and to justify the formulated three hypotheses. Statistical tests on correlations and regression analysis were manipulated to test the hypothesized causal model. Secondly, field research in the form of observation, interviews, and focus group discussion were carried out to discover the pattern and the role of social institutions, and the reasons articulated by the respondents on their state of poverty, and the practice of social capital. The findings of the study thus showed that the incidence poverty are caused by external structural factors namely the changes in government policies related to economic and political matters. On the other hand, patterns of poverty incidence followed the individual characteristics, namely the level of education, age, and obligations towards religion, and parents' level of of income and education. The result of the field finding also indicated that the respondents' opinions were influenced by Javanese cultural values. The findings indicated that poverty reduction does not correlate with bonding social capital, but, it does correlates with bridging and linking. Thus far, lessons revealed by the finding indicate that to alleviate poverty, direct and indirect measures must be taken. It also revealed that, there were five institutions involved in creating bonding social capital, five involved in creating bridging, and two involved in creating linking social capital. Nevertheless, the natures of the social institutions creating social capital differ from each other. The results showed that respondents' degree of bonding are high, of bridging are moderate, and their linking are low. Overall, the results clearly indicated that education, income and preference of religion have no direct influence towards the degree of bonding. However, the degree of bridging is strongly influenced by family monthly income and educational level. Age, however, have a negative relationship with bonding, bridging as well as linking social capital.